2007
DOI: 10.4012/dmj.26.38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Properties in Composite Resins on Light Transmittance Characteristics and Color

Abstract: The purpose of this investigation was to examine the effect of filler particle size and shape as well as filler content on light transmittance characteristics and color of experimental composite resins. A mixture of 30 mol% Bis-GMA and 70 mol% TEGDMA was prepared as a base monomer and to which a photoinitiator (camphorquinone) and a co-initiator (N,Ndimethylaminoethyl methacrylate) were added. Four different irregular-and spherical-shaped filler types with an average particle size of 1.9-11.1 μm were added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 19 publications
6
109
2
5
Order By: Relevance
“…Since dental resin-based composites consist of heterogeneous substances, including both resin and fillers, light is scattered at the resin-filler interface according to differences in the refractive indices of the individual compounds (29). Correspondingly, light transmittance in dental resin-based composites has been shown to decrease with increased filler content and for irregular filler shapes as a result of an increased specific surface area between the fillers and resin (30). Furthermore, for filler sizes ranging from 0.05-2 μm it has been demonstrated that reduced light transmission occurs due to the inability of the particles that are smaller than the wavelength of incident blue light to scatter the blue light (31).…”
Section: Discussionmentioning
confidence: 99%
“…Since dental resin-based composites consist of heterogeneous substances, including both resin and fillers, light is scattered at the resin-filler interface according to differences in the refractive indices of the individual compounds (29). Correspondingly, light transmittance in dental resin-based composites has been shown to decrease with increased filler content and for irregular filler shapes as a result of an increased specific surface area between the fillers and resin (30). Furthermore, for filler sizes ranging from 0.05-2 μm it has been demonstrated that reduced light transmission occurs due to the inability of the particles that are smaller than the wavelength of incident blue light to scatter the blue light (31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the filler causes changes in the physical characteristics of light transmittance that influenced the color of resin composites. 27,28 The fact that the Estenia C&B indirect composite, which is a hybrid composite, exhibited the lowest light transmission values at both thicknesses can be attributed to the higher percentage of ceramic microfillers (92 wt%) with a particle size of 2 μm.…”
Section: Discussionmentioning
confidence: 99%
“…The wide and deep trough observed around 470 nm for all materials may have been due to light absorbance by the photoinitiator contained in the materials because the wavelength range was similar to the representative absorbance wavelength range of camphorquinone, a conventional photoinitiator often used in light-activated dental materials 15) . Our previous study reported that the filler particle in the composite resin played an important role for the light transmittance characteristics, including light diffusion characteristics, and color of the material 16) . Although limited information is available on the exact nature of chemical composition of pit and fissure sealants, the significant differences in the light transmittance would be likely caused by differences in the optical properties and the shape of filler particles, as well as particle size and filler content.…”
Section: Discussionmentioning
confidence: 99%